Evidence of neurodegeneration in individuals with only mildly elevated blood pressure - Jung, Susanne; Bosch, Agnes; Kohler, Nikolas; Ott, Christian; Kannenkeril, Dennis; Dienemann, Thomas; Harazny, Joanna M.; Michelson, Georg; Schmieder, Roland (Journal of Hypertension, 2019)
OBJECTIVE: Initiation of antihypertensive drug treatment in low-risk individuals with grade 1 hypertension is under debate. The aim of this study was to examine the impact of mildly elevated blood pressure (BP) on early neurodegenerative processes independent of ageing. METHODS: Sixty-two individuals were included in this study: 25 young (aged <40 years) and 37 older (aged ≥40 years) individuals at low cardiovascular risk and grade 1 hypertension at most. Macular retinal layer volumes of both eyes were determined by SD-OCT. Total retinal volume but also each inner retinal layer volume separately including retinal nerve fiber layer (RNFL), ganglion cell layer (GCL), inner plexiform layer (IPL), and GCL-IPL were measured in each individual. RESULTS: Retinal layer volumes were lower among older individuals compared with young individuals (RNFL right eye: P = 0.037/left eye: P = 0.021; GCL and GCL-IPL: both eyes P < 0.001; IPL right eye: P = 0.005/left eye: P = 0.002; total retinal volume: both eyes P = 0.002) and there was an inverse correlation between retinal layer volumes and age. Partial correlation analysis, excluding age as a cofactor, revealed an inverse association between retinal layer volumes and DBP. In multiple regression analysis, DBP was identified as a determinant of retinal neurodegenerative processes. CONCLUSION: In the current study, we observed an inverse association between retinal neurodegenerative processes and DBP, suggesting that BP-lowering therapy by early antihypertensive drug-treatment might be beneficial to avoid early neurodegeneration.
EVALuna2:203883